The Brain in Oral Clefting: A Systematic Review With Meta-Analyses - Sándor-Bajusz, Kinga A.; Sadi, Asaad; Varga, Eszter; Csábi, Györgyi; Antonoglou, Georgios N.; Lohner, Szimonetta (Frontiers in Neuroanatomy, 2022)
Background: Neuroimaging of individuals with nonsyndromic oral clefts have revealed subtle brain structural differences compared to matched controls. Previous studies strongly suggest a unified primary dysfunction of normal brain and face development which could explain these neuroanatomical differences and the neuropsychiatric issues frequently observed in these individuals. Currently there are no studies that have assessed the overall empirical evidence of the association between oral clefts and brain structure. Our aim was to summarize available evidence on potential brain structural differences in individuals with nonsyndromic oral clefts and their matched controls. Methods: Five databases were systematically searched in September 2020 for case-control studies that reported neuroimaging in individuals with nonsyndromic oral clefts and healthy controls. Duplicate study selection, data extraction, random effects meta-analyses of mean differences (MDs) and their 95% confidence intervals (95% CI) were performed in order to compare global and regional brain MRI volumes. Results: Ten studies from 19 records were included in the review. A total of 741 participants were analyzed. A moderate to high risk of bias was determined for the included studies. The cerebellum (MD: -12.46, 95% CI: -18.26, -6.67, n=3 studies), occipital lobes (MD:-7.39, 95% CI: -12.80, -1.99, n=2 studies), temporal lobes (MD: -10.53, 95% CI: -18.23, -2.82, n=2 studies) and total grey matter (MD: -41.14; 95% CI: -57.36 to -24.92, n=2 studies) were significantly smaller in the cleft group compared to controls. Conclusion: There may be structural brain differences between individuals with nonsyndromic oral clefts and controls based on the available evidence. Improvement in study design, size, methodology and participant selection could allow a more thorough analysis and decrease study heterogeneity.